1978
DOI: 10.1161/01.cir.57.6.1091
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of enzyme levels by propranolol after acute myocardial infarction.

Abstract: SUMMARY The effect of propranolol (0.1 mg/kg intravenously followed by 320 mg given over 27 hour orally) on serum levels of creatine kinase enzyme was studied in a randomized trial involving 95 patients seen within 12 hours of onset of symptoms of uncomplicated myocardial infarction. In 15 patients who were treated with propranolol within 4 hours of onset, and who eventually developed pathological Q waves, peak measured enzyme levels were 27% (P < 0.0125) lower than in 19 control patients who were also seen TH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

1978
1978
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(38 citation statements)
references
References 13 publications
0
37
0
1
Order By: Relevance
“…The advantages of treating myocardial infarction with systemic hypertension, a situation associated with high serum catecholamine levels, by adrenoceptor blockade, were not apparent in a previously described (Kelly et al, 1973) (Peter et al, 1978). Similarly, problems have been encountered with other pharmacological agents.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The advantages of treating myocardial infarction with systemic hypertension, a situation associated with high serum catecholamine levels, by adrenoceptor blockade, were not apparent in a previously described (Kelly et al, 1973) (Peter et al, 1978). Similarly, problems have been encountered with other pharmacological agents.…”
Section: Discussionmentioning
confidence: 95%
“…However, ac-adrenoceptor blockade with phentolamine in these circumstances is relatively ineffective in reducing systemic BP in those patients with pre-existing hypertension and, moreover, while satisfactorily lowering left ventricular end diastolic BP, increases heart rate and can worsen myocardial ischaemia (Kelly et al, 1973). padrenoceptor blockade on the other hand lowers systemic BP and heart rate, but may elevate left ventricular filling pressure (Peter et al, 1978).…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Therefore, beta adrenergic blockade has gained increasing interest as therapeutic intervention in the acute state of myocardial infarction. Propranolol has been shown to be beneficial in experimental coronary occlusion (7) and in human myocardial infarction for a selected patient group (8)(9)(10). Recent studies have demonstrated, however, that propranolol increased plasma catecholamine contents in several clinical conditions (11)(12)(13), and thus caused concern about its use in acute myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…Using serial serum creatine kinase (CK) measurements, all events of the CK time-activity curve (rise, peak, and decay) occurred significantly later compared to those of the untreated group. Peter et al (62) demonstrated in a randomized trial of patients with uncomplicated myocardial infarction that both peak serum CK levels and total calculated serum CK appearances were significantly reduced by approximately 30% if propranolol was given intravenously in a dose of 0.1 mg/kg within 4 h of the onset of chest pain. In a later study on 20 randomly selected patients within 4 h of the onset of suspected myocardial infarction, propranolol adminstration (0.1 mg/kg i.v.…”
Section: H S Mueller Et Al: Propranolol In Acute Myocardial Infarcmentioning
confidence: 99%